Diagnosis of malignant tumors of female breast cancer by transmission optical tomography - I. V. Pyanov (ABV-press, 2014)
A review of the literature on diagnostic systems for the detection of breast cancer by optical tomography was presented. The actuality of the method of transmission of optical tomography and its advantages over existing methods of medical diagnosis of cancer have been substanti- ated. We have analyzed tomographic systems used for the diagnosis of breast cancer. The basic advantages and disadvantages of tomograph- ic systems using various types of radiation have been indicated. The results of review can be used in the development of technique for optical transmission tomography.